Studies on the performance of UC Davis chimney dryer on drying of Jackfruits leather - Halima Khatun; Mohammad Abdur Rahim; Md Ashraful Islam (Fundamental and Applied Agriculture, 2019)
An observation on the performance of UC Davis chimney drier on drying of leather was carried out at BAU-GPC, Department of Horticulture, Bangladesh Agricultural University, Mymensingh, during February 2017-October 2017.Jackfruits leather were trailed by two varieties. The collected jackfruits were peeled off the hard rind of the jackfruits, then extract the juice manually and maintained the desirable thickness layer i.e. 1.0 cm, 0.5 cm on the tray. Some trays were placed under UC Davis chimney drier for study and some trays were placed on open with net condition as control. Required times to dry was (8.25 days) for jackfruits leather dry under UCD than open with net condition (12.75 days). Solar dry matter content (15.84%), final TSS (38.17% Brix), storage time (247.75 days) was higher in UCD than open with net condition (13.67%, 0.00% and 24.42 days). Relative humidity (61.25%) and moisture content (86.33%) was high in open with net than UCD (44.79% and 84.16% respectively).Thickness of 0.5cm required less (9.33 days) to dry than 1.0cm (11.67days). 0.5cm solar dry matter was high (18.22%), longer storage (137.42 days) than 1.0cm (11.29% and 134.75 days). Panel test was high (55.00% aroma, 57.00% color and 51.00% taste) under UCD than open with net condition (35.83%, 34.00% and 33.34% respectively). Thickness of 0.5cm was high (50.00% aroma, 47.50% color and 36.33% taste) than 1.0cm (40.48%, 44.00% and 36.33% respectively) thickness of jackfruits leather. [Fundam Appl Agric 2019; 4(1.000): 661-670]